2009
DOI: 10.1248/bpb.32.1906
|View full text |Cite
|
Sign up to set email alerts
|

6-Deoxy-6-[<sup>131</sup>I]iodo-<small>L</small>-ascorbic Acid for the <i>in Vivo</i> Study of Ascorbate: Autoradiography, Biodistribution in Normal and Hypolipidemic Rats, and in Tumor-Bearing Nude Mice

Abstract: Over the past few decades, a number of radiopharmaceuticals for noninvasive imaging of the adrenal glands by the nuclear imaging technique have been evolved, designed by targeting specific metabolic or synthetic processes within the gland.1,2) Among the current developments and the expansion of new molecular imaging modalities and specific probes, adrenal scintigraphy using more specific radiotracers to obtain functional information for tissue characterization is still challenging. 3,4)The adrenal gland is amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…There was a somewhat slower clearance of the radioactivity from the blood when compared to 6-18 FAsA 10-13) and 6-131 IAsA 14,15) studied previously. The accumulation of radioactivity in selected organs was highest in the kidneys>liver>lungs>adre nals>heart at 2 min postinjection and then the radioactivity levels gradually decreased with time, similar to those seen for [6][7][8][9][10][11][12][13][14][15][16][17][18] FAsA and 6-131…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…There was a somewhat slower clearance of the radioactivity from the blood when compared to 6-18 FAsA 10-13) and 6-131 IAsA 14,15) studied previously. The accumulation of radioactivity in selected organs was highest in the kidneys>liver>lungs>adre nals>heart at 2 min postinjection and then the radioactivity levels gradually decreased with time, similar to those seen for [6][7][8][9][10][11][12][13][14][15][16][17][18] FAsA and 6-131…”
Section: Resultsmentioning
confidence: 55%
“…Moreover, tumor accumulation in the fibrosarcoma was not significant, also similar to those of [6][7][8][9][10][11][12][13][14][15][16][17][18] FAsA and IAsA. Recent studies have shown that high-grade tumor tissue has reduced capacity to accumulate AsA relative to normal tissue.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Data in mice showed increased radioactive ascorbate uptake in adrenal glands, compared to adrenocortical or adrenal medulla tumors, and adrenal uptake was sensitive to the ascorbate transport blocking agent sulfinpyrazone (67). In a mouse neuroblastoma cell line, SVCT2 was found to have two different transport kinetics ( K m of 13 and 105 µM), and transport could be inhibited with flavonoids (68).…”
Section: Sodium-dependent Vitamin C Transportermentioning
confidence: 99%